Synthesis of freestanding few-layer graphene in microwave plasma: The role of oxygen. (January 2022) - Fortugno, Paolo; Musikhin, Stanislav; Shi, Xian; Wang, Hai; Wiggers, Hartmut; Schulz, Christof
Abstract: We systematically studied the role of oxygen in gas-phase synthesis of graphene in atmospheric hydrocarbon-fed microwave plasmas. Oxygen is introduced through the use of alcohols, and mixtures of ethylene and water. These reactants were contrasted with oxygen-free hydrocarbon reactants, including ethylene and toluene. Solid materials were collected at the plasma reactor exit and characterized. Gas-phase temperature and key species concentrations were measured using in situ Fourier-transform infrared absorption and emission spectroscopy inside the reactors. Ethanol resulted in pure few-layer graphene formation, in agreement with previous studies. In contrast, ethylene fed at the same flow rate produced a mixture of carbon allotropes. A shift towards graphene formation is observed when water is added to ethylene, or when the flow rate of ethylene is cut to half. Simulations suggest that reactants undergo rapid chemical reactions in the plasma front and the mixture composition in and immediately after the plasma is in chemical equilibrium. The primary factor that controls graphene growth appears to be the total amount of carbon available in the growth region. Oxygen, through CO formation, modulates the amount of acetylene and other growth species, while other factors require further study. Graphical abstract: Image 1